Thermomechanical properties of rare-earth-doped AlN for laser gain media: The role of grain boundaries and grain size. (March 2015) - Wieg, A.T.; Kodera, Y.; Wang, Z.; Dames, C.; Garay, J.E.
Abstract: The low thermal conductivity and poor fracture toughness of traditional laser gain media (rare-earth-doped single crystals) limits the overall power deliverable from a laser system. We present an investigation of the thermomechanical properties of a promising laser gain candidate, Tb-doped aluminum nitride (Tb:AlN). We pay special attention to the effect of the average grain size and the dopant segregation at the grain boundaries on the relevant properties: Vickers hardness, fracture toughness and thermal conductivity. We find that all properties are affected by grain boundaries and/or dopant segregation. However, the thermal conductivity is significantly more affected than the mechanical properties and therefore dominates the thermal shock figure of merit, R s . We obtained a thermal shock figure of merit in Tb:AlN more than 60 times that of the state-of-the-art laser gain material Nd:YAG.